2001
DOI: 10.1046/j.1461-9563.2001.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of traps of six different designs to capture pine sawyer beetles (Coleoptera: Cerambycidae)

Abstract: Summary1 Sawyer beetles (Coleoptera: Cerambycidae) and metallic wood‐boring beetles (Coleoptera: Buprestidae) attack recently killed or felled trees. They are attracted to potential hosts by volatiles and possibly by visual cues. We examined traps of six different designs to determine the role of silhouette and shape in the capture of pine sawyer beetles, Monochamus L.2 Traps with a round black cylinder, a single vane (clear or black), or cross vanes (clear or black) all mounted above a pan were compared to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 18 publications
4
48
0
Order By: Relevance
“…The importance of visual cues in host selection behavior has been reported in many phytophagous insects [2,4,10,19,24], and studies have demonstrated that visual cues are used in the host-finding behavior of Cerambycid species [8,17,18]. Further studies on how visual cues are utilized in combination with attraction to host volatiles should clarify the host selection precess of M. alternatus.…”
Section: Discussionmentioning
confidence: 90%
“…The importance of visual cues in host selection behavior has been reported in many phytophagous insects [2,4,10,19,24], and studies have demonstrated that visual cues are used in the host-finding behavior of Cerambycid species [8,17,18]. Further studies on how visual cues are utilized in combination with attraction to host volatiles should clarify the host selection precess of M. alternatus.…”
Section: Discussionmentioning
confidence: 90%
“…In each year, a factorial experiment was run with three trap types, either baited with two spruce blend lures (Ϸ300 mg/d) or left unbaited to serve as controls, for a total of six treatments. In 2001, the trap types were (1) 12-unit multiple funnel trap (Lindgren 1983, Phero Tech 1997; (2) Intercept panel trap (IPM Technologies, Portland, OR); and (3) cross-vane pan trap (de Groot and Nott 2001). In 2002, the funnel trap was replaced with IPM-Intercept panel traps that had been coated with Rain-X (Pennzoil-Quaker State, Burlington, Ontario, Canada).…”
Section: Effect Of Spruce Blend and Trap Design On Catchmentioning
confidence: 99%
“…Positive response to monoterpenes, ethanol, and other conifer volatiles has been shown for some species of cerambycids (Gardiner 1957, Ikeda et al 1980, Phillips et al 1988, Ché nier and Philogè ne 1989b, Allison et al 2001, 2003, de Groot and Nott 2001, Morewood et al 2002a), but little is known of the BSLBÕs response to host volatiles. In 1990, BSLB adults (originally misidentiÞed as the native beetle, T. cinnamopterum Kirby) were captured on turpentinebaited traps intended to capture bark beetles in Point Pleasant Park (Robertson 1990).…”
mentioning
confidence: 99%
“…It has been shown that traps with black silhouettes are significantly more effective in capturing woodborer cerambycids, including M. scutellatus, than traps with clear vanes (de Groot and Nott, 2001). In another experiment, black-panel cross-vane traps were more effective than dry multiplefunnel traps for capturing several North American Monochamus species .…”
Section: Introductionmentioning
confidence: 99%